Wear-resistant coating for inner wall of slender pipe and preparation method thereof
Through the tube magnetron sputtering technology, the problem of insufficient density and uniformity of the inner wall coating of the slender tube is solved, and the preparation of a high-performance wear-resistant coating is realized, which improves the wear resistance and safety of the slender tube. Suitable for pipes of different sizes.
Patent Information
- Application Number
- CN202411418978.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the wear-resistant coating of the inner wall of the slender tube is insufficient in compactness, thickness and uniformity, and poor process flexibility, which poses safety risks and risks of hydrogen embrittlement cracking.
Using tube magnetron sputtering technology, through ion cleaning, preparation of binding force layers and nanocoatings, high-power pulse magnetron sputtering or deep-oscillating magnetron sputtering technology, avoid flammable and explosive gases, and adapt to different diameters and The length of the slender tube achieves a wear-resistant coating with high density, high uniformity and high performance.
We prepare a wear-resistant coating with nanohardness of 15-45GPa, high uniformity, excellent Rockwell indentation bonding and fracture toughness, and low friction coefficient, which improves the wear resistance and safety of the slender tubes and is suitable for mass production.
Smart Images

Figure CN119287326A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pipeline wear-resistant coatings, and in particular to a wear-resistant coating for the inner wall of a slender pipe and a preparation method thereof. Background Art
[0002] Slender tubes are widely used in many industrial applications, especially in the fields of nuclear energy, chemical industry, aviation, etc. The application of wear-resistant coatings is of great significance for improving the service life and performance of slender tubes. In the prior art, although a variety of wear-resistant coating materials (such as Cr, high entropy alloys, transition metal nitrides and carbides, etc.) have been widely studied and applied, there are still some problems to be solved in their preparation process.
[0003] Currently, commonly used coating preparation methods include laser cladding, plasma spraying and chemical vapor deposition. However, these methods have the following disadvantages in the application of wear-resistant coatings on the inner wall of slender tubes: (1) Insufficient coating density: The existing preparation methods often lead to excessively high coating porosity, which reduces the bonding force and overall strength of the coating, thereby affecting the wear resistance; (2) Insufficient coating thickness and uniformity: In the preparation of coatings on the inner wall of slender tubes, it is difficult to achieve uniform distribution and appropriate thickness of the coating, which usually leads to the coating being too thick in some areas and too thin in other areas, affecting the overall effect; (3) Poor process flexibility: The coating preparation equipment in the existing technology generally needs to be adjusted for specific tube diameters and lengths, and it is difficult to adapt to slender tubes of different diameters and lengths, limiting its scope of application; (4) Safety issues: Some traditional methods use flammable and explosive gases (such as methane, acetylene, etc.), which increases the safety risks of the process, and these flammable gases may also cause the risk of hydrogen embrittlement cracking of the coating in subsequent use.
[0004] Therefore, there is an urgent need for a wear-resistant coating for the inner wall of a slender tube and a preparation method thereof to solve the above problems, to prepare a wear-resistant coating with high density, high uniformity and high performance, to ensure long-term protection of the coating and to improve the wear resistance of the slender tube. Summary of the invention
[0005] The object of the present invention is to provide a wear-resistant coating for the inner wall of a slender tube and a preparation method thereof, so as to solve the problems of insufficient density, insufficient thickness and insufficient uniformity of the wear-resistant coating for the inner wall of a slender tube in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a wear-resistant coating on the inner wall of a slender tube, comprising the following steps:
[0008] (1) cleaning the elongated tube, then placing an ion source at the center of the elongated tube, placing a target material in the elongated tube, sealing both ends of the elongated tube, setting a vacuum circuit and a gas circuit, and obtaining a tubular magnetron sputtering device;
[0009] (2) sequentially performing ion cleaning on the tubular magnetron sputtering device, preparing a bonding layer and a nano coating, and obtaining a wear-resistant coating;
[0010] The bonding layer and the nano coating are prepared by using a high-power pulsed magnetron sputtering technique or a deep oscillation magnetron sputtering technique.
[0011] Preferably, in step (1), the elongated tube has a length-to-diameter ratio of ≥12:1, an inner diameter of ≥40 mm, and a length of ≥500 mm.
[0012] Preferably, in step (1), the target material comprises one or more of Cr, Ti, Al, TiAlSi, TiAl, TiVSi, TiSi, Si, CrAl and carbon.
[0013] Preferably, in step (1), the length of the target material is the same as the length of the slender tube; and the ratio of the inner diameter of the slender tube to the diameter of the target material is 4:2-3.
[0014] Preferably, in step (2), during ion cleaning, the tubular magnetron sputtering device is first evacuated to a vacuum degree of less than 1×10 -4 Pa is then ion cleaned.
[0015] Preferably, the process parameters of the ion cleaning are: argon gas flow rate of 80 to 180 sccm, gas pressure of 0.2 to 3 Pa, voltage of -500 to 800 V, frequency of 80 to 120 kHz, and ion cleaning time of 30 to 90 min.
[0016] Preferably, in the step (2), high-power pulsed magnetron sputtering is started to prepare the bonding layer, and the process parameters are: target voltage pulse width is 1 to 5 μs, peak power is 6 to 8 kW, argon gas flow rate is 60 to 130 sccm, gas pressure is 0.3 to 2 Pa, voltage is -30 to -200 V, high energy bombardment is 1 to 5 min, and then the voltage of the negative bias power supply is reduced to -60 to -100 V.
[0017] Preferably, in the step (2), deep oscillation magnetron sputtering is started to prepare the nanocoating, and the process parameters are: pulse switching time ratio is 1-65s / 10-50μs, average power is 0.5-2kW, gas pressure is 0.2-3Pa, argon flow rate is 50-180sccm, nitrogen flow rate is 40-180sccm, negative bias power supply voltage is -20--100V, and preparation process time is 60-150min.
[0018] The present invention also provides a wear-resistant coating prepared by the above-mentioned method for preparing the wear-resistant coating on the inner wall of a slender tube, wherein the nanohardness of the wear-resistant coating is 15 to 45 GPa, H / E* (E* is the effective Young's modulus) ≥ 0.1, uniformity ≥ 96%, H 3 / E* 2 ≥0.3, Rockwell indentation bonding strength ≥HF1, fracture toughness K IC ≥3MPa·m 1 / 2 , friction coefficient ≤0.3.
[0019] Beneficial effects of the present invention:
[0020] (1) The wear-resistant coating prepared by the present invention has the characteristics of high strength, toughness, integration and high uniformity.
[0021] (2) The present invention places the ion source and the target material in a slender tube fitting, and the slender tube fitting is a vacuum chamber, which can adapt to the preparation of various slender tube inner wall coatings, and the process is flexible and adjustable.
[0022] (3) The method for preparing the wear-resistant coating on the inner wall of the slender tube provided by the present invention has the advantages of fast deposition rate, simple operation, low cost and suitability for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a graph showing the indentation bonding strength test of the Cr / CrCN wear-resistant coating prepared in Example 1;
[0024] Figure 2 This is a graph showing the indentation bonding strength test of the Ti / TiAlSiN wear-resistant coating prepared in Example 2;
[0025] Figure 3 This is a test diagram of the micron indentation of the Cr / CrCN wear-resistant coating prepared in Example 1;
[0026] Figure 4 This is a test diagram of the micron indentation of the Ti / TiAlSiN wear-resistant coating prepared in Example 2;
[0027] Figure 5 The friction and wear curve of the Cr / CrCN wear-resistant coating prepared in Example 1;
[0028] Figure 6 This is a friction and wear curve diagram of the Ti / TiAlSiN wear-resistant coating prepared in Example 2;
[0029] Figure 7 This is a test sample diagram of Example 1;
[0030] Figure 8 This is a test sample diagram of Example 2;
[0031] Fig. 9 is a schematic diagram of a tubular magnetron sputtering device of the present invention;
[0032] Fig.10 is a schematic diagram of the Cr / C composite target in Example 1, wherein x represents the length of Cr and y represents the length of C;
[0033] Fig.11 This is a schematic diagram of placing the substrate on the inner wall of a slender tube. The workpiece is the slender tube and the test piece is the substrate. DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a wear-resistant coating on the inner wall of a slender tube, comprising the following steps:
[0035] (1) cleaning the elongated tube, then placing an ion source at the center of the elongated tube, placing a target material in the elongated tube, sealing both ends of the elongated tube, setting a vacuum circuit and a gas circuit, and obtaining a tubular magnetron sputtering device;
[0036] (2) sequentially performing ion cleaning on the tubular magnetron sputtering device, preparing a bonding layer and a nano coating, and obtaining a wear-resistant coating;
[0037] The bonding layer and the nano coating are prepared by using a high-power pulsed magnetron sputtering technique or a deep oscillation magnetron sputtering technique.
[0038] In the present invention, in step (1), the length-to-diameter ratio of the slender tube is ≥12:1, preferably 12.5:1, the inner diameter is ≥40 mm, preferably 40 mm; and the length is ≥500 mm, preferably 500 mm.
[0039] In the present invention, flanges are used to fix the target material and both ends of the slender tube are sealed; the slender tube can be connected to a bias power supply and a sputtering power supply; and a circulating cooling water loop is provided on the slender tube.
[0040] In the present invention, in step (1), the target material comprises one or more of Cr, Ti, Al, TiAlSi, TiAl, TiVSi, TiSi, Si, CrAl and carbon, preferably a Cr target, a Ti target, a combination target of CrC, or a combination target of TiAlSi.
[0041] The present invention can use graphite target materials and does not use inflammable and explosive gases such as methane and acetylene, thereby reducing the safety of the process and the risks of subsequent hydrogen embrittlement and cracking of the coating. The hydrogen-free carbon-based nanocoating prepared by this method can achieve high-performance protection at high temperatures above 800°C, and can effectively replace DLC coatings prepared by processes such as chemical vapor deposition and ion plating.
[0042] In the present invention, in the step (1), the length of the target material is the same as the length of the slender tube; the ratio of the inner diameter of the slender tube to the diameter of the target material is 4:2-3, preferably 4:2.5.
[0043] In the present invention, in step (2), during ion cleaning, the tubular magnetron sputtering device is first evacuated to a vacuum degree of less than 1×10 -4 Pa is then ion cleaned.
[0044] In the present invention, the process parameters of the ion cleaning are: argon gas flow rate is 80-180sccm, preferably 100sccm, 120sccm, 150sccm, gas pressure is 0.2-3Pa, preferably 0.2Pa, 1Pa, 2Pa, 3Pa, voltage is -500-800V, preferably -500V, -300V, 400V, 800V, frequency is 80-120kHz, preferably 80kHz, 100kHz, 110kHz, ion cleaning time is 30-90min, preferably 30min, 60min, 90min.
[0045] In the present invention, in the step (2), high-power pulsed magnetron sputtering is started to prepare the bonding layer, and the process parameters are: the target voltage pulse width is 1 to 5 μs, preferably 5 μs and 3 μs, the peak power is 6 to 8 kW, preferably 6 kW and 8 kW, the argon gas flow rate is 60 to 130 sccm, preferably 60 to 100 sccm, the gas pressure is 0.3 to 2 Pa, preferably 0.3 Pa, 1 Pa, 2 Pa, the voltage is -30 to -200 V, preferably -30 V and -100 V, high energy bombardment is performed for 1 to 5 minutes, and then the voltage of the negative bias power supply is reduced to -60 to -100 V.
[0046] In the present invention, in the step (2), deep oscillation magnetron sputtering is started to prepare the nano coating, and the process parameters are: pulse switching time ratio is 1-5μs / 10-50μs, average power is 0.5-2kW, gas pressure is 0.2-3Pa, preferably 0.2Pa, 1Pa, 3Pa, argon flow rate is 50-180sccm, preferably 60sccm, 120sccm, 180sccm, nitrogen flow rate is 40-180sccm, preferably 40sccm, 80sccm, 120sccm, 180sccm, voltage is -20--100V, preferably -20V, -80V, -100V, and preparation process time is 60-150min, preferably 60min, 100min, 120min, 150min.
[0047] In the present invention, the pulse width affects the cooling rate of the deposition, and thus affects the microstructure and phase change behavior of the coating. A pulse width that is too long may introduce a higher thermal impact, causing the coating to crack. A negative bias that is too high may introduce more internal stress, causing the coating to crack or peel. Negative bias adjustment within a reasonable range can control the grain size, optimize the microstructure, and significantly improve the mechanical properties of the coating.
[0048] The present invention also provides a wear-resistant coating prepared by the above-mentioned method for preparing the wear-resistant coating on the inner wall of the slender tube, wherein the nano hardness of the wear-resistant coating is 15 to 45 GPa, H / E*≥0.1, uniformity ≥96%, H 3 / E* 2 ≥0.3, Rockwell indentation bonding strength ≥HF1, fracture toughness K IC ≥3MPa·m 1 / 2 , friction coefficient ≤0.3.
[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] Example 1
[0051] Cleaning of the slender tube and substrate: Place the slender tube and experimental substrate in an acetone container and clean them for 60 minutes using an ultrasonic cleaner. Take them out and blow dry them with compressed air and set them aside for use. The length of the slender tube is 500 mm and the inner diameter is 40 mm.
[0052] Substrate installation: Mount the substrate on the inner wall of the slender tube, refer to Fig.11 Place it, and then place the slender tube on the sample platform.
[0053] Ion cleaning: vacuumize in a closed environment until the vacuum degree is less than 1×10 -4 Pa, a pulsed DC power supply was used to connect the slender tube, and the pulse parameters were set as follows: argon flow rate of 150 sccm, gas pressure of 3 Pa, voltage of -500 V, frequency of 100 kHz, and ion cleaning time of 60 min.
[0054] Preparation of Cr metal bonding layer: Using Cr palladium, start high-power pulsed magnetron sputtering, set the pulse parameters as follows: pulse width of 5μs, peak power of 6kW, voltage of -100V, gas pressure of 2Pa, argon flow rate of 100sccm, high-energy bombardment for 5min, and then reduce the voltage to -60V to obtain a Cr metal bonding layer with a thickness of 200nm.
[0055] Preparation of CrCN nano-coating: using a Cr / C combined target, in which Cr and C alternate, and the length ratio of Cr and C is x:y=3:1, starting deep oscillation magnetron sputtering, and setting the process parameters: pulse switching time ratio of 5μs / 50μs, average power of 2kW, gas pressure of 3Pa, argon flow rate of 180sccm, nitrogen flow rate of 180sccm, voltage of -100V, time of 60min, after completing the preparation of the CrCN nano-coating, wait for 60min before taking the sample to obtain the wear-resistant coating.
[0056] Example 2
[0057] Cleaning of the slender tube and substrate: Place the slender tube and experimental substrate in an acetone container and clean them for 60 minutes using an ultrasonic cleaner. Take them out and blow dry them with compressed air and set them aside for use. The length of the slender tube is 500 mm and the inner diameter is 40 mm.
[0058] Substrate installation: Mount the substrate on the inner wall of the slender tube, refer to Fig.11 Place it, and then place the slender tube on the sample platform.
[0059] Ion cleaning: vacuumize in a closed environment until the vacuum degree is less than 1×10 -4 Pa, a pulsed DC power supply was used to connect the slender tube, and the pulse parameters were set as follows: argon flow rate was 120 sccm, gas pressure was 0.2 Pa, voltage was -800 V, frequency was 80 kHz, and ion cleaning time was 90 min.
[0060] Preparation of Ti metal bonding layer: Use titanium palladium, start high-power pulsed magnetron sputtering, set the pulse parameters as follows: pulse width 3μs, peak power 8kW, voltage -30V, gas pressure 0.3Pa, argon flow rate 60sccm, high energy bombardment for 1min, and then reduce the voltage to -60V to obtain a Ti metal bonding layer with a thickness of 500nm.
[0061] Preparation of TiAlSiN nano-coating: A TiAlSi composite target was used, in which Ti, Al, and Si were alternating, and the length ratio of Ti, Al, and Si was x:y:z=8:1:1. Deep oscillation magnetron sputtering was started, and the process parameters were set as follows: the pulse switching time ratio was 2μs / 10μs, the average power was 0.5kW, the gas pressure was 0.2Pa, the argon flow rate was 60sccm, the nitrogen flow rate was 40sccm, the voltage was -20V, and the time was 150min. After the preparation of the TiAlSiN nano-coating was completed, wait for 60min before taking the sample to obtain the wear-resistant coating.
[0062] The performance of the wear-resistant coatings prepared in Examples 1 and 2 was verified. Five samples were tested in each example. The test method was as follows:
[0063] (1) Hardness: The test was conducted using a nanoindenter with an indentation depth of 300 nm.
[0064] (2) HRC indentation bonding strength:
[0065] Prepare the sample: Choose appropriate sample material and ensure the sample surface is smooth and clean.
[0066] Set up the test equipment: Use a Rockwell hardness tester, select an appropriate indenter and use a load of 150kgf.
[0067] Apply load: Through the control system of the Rockwell hardness tester, the indenter is placed vertically on the sample surface and the load is applied within the set time.
[0068] Maintain the applied load for a specified time (usually about 15 seconds) to ensure that the indenter forms a stable indentation.
[0069] Unload: Unload the pressure head.
[0070] Analysis results: The indentation area was observed under a microscope and the shape and size changes of the indentation were evaluated to judge the bonding quality between the coating and the substrate.
[0071] (3) Micron indentation:
[0072] Prepare samples: Select appropriate coating samples, ensure that their surfaces are smooth and prepared according to standard dimensions to ensure accurate measurement.
[0073] Micron indentation test: Use a Vickers hardness tester to apply a load of 10g at different locations on the coating for testing.
[0074] Analyze the indentation characteristics:
[0075] Observe the structural changes of the coating at the indentation site. The microstructure around the indentation can be examined using a microscope, with special attention paid to whether cracks or other structural damage appear around the indentation, which can indicate the toughness of the coating.
[0076] (4) Friction and wear curve
[0077] Sample installation: Fix the sample to be tested on the reciprocating friction workbench to ensure the sample position is stable.
[0078] A stainless steel ball is selected as the friction material and fixed in the corresponding position.
[0079] Set experimental parameters: Set relevant parameters according to the experimental requirements, friction speed is 1Hz, friction load is 2N, reciprocating stroke is 5mm, and experimental time is 60min.
[0080] Start the test: Start the testing machine and start the reciprocating friction test
[0081] End the test and record the data.
[0082] The test results are shown in Table 1 and Table 2:
[0083] Table 1 Test results of Cr / CrCN wear-resistant coating of Example 1
[0084] sample Binding force Hardness[GPa] <![CDATA[Fracture toughness [MPa·m 1 / 2 > Friction coefficient <![CDATA[1 # Cr / CrCN]]> ≥HF1 28.8GPa 7.5 0.091 <![CDATA[2 # Cr / CrCN]]> ≥HF1 29.2GPa 6.8 0.089 <![CDATA[3 # Cr / CrCN]]> ≥HF1 29.6GPa 7.8 0.087 <![CDATA[4 # Cr / CrCN]]> ≥HF1 29.3GPa 7.4 0.090 <![CDATA[5 # Cr / CrCN]]> ≥HF1 29.0GPa 6.9 0.092
[0085] Table 2 Test results of the wear-resistant coating of Ti / TiAlSiN of Example 2
[0086]
[0087]
[0088] Figure 1 This is an indentation bonding strength test diagram of the Cr / CrCN wear-resistant coating prepared in Example 1. It can be seen that the Cr / CrCN wear-resistant coating has no cracks or shedding, indicating that the bonding strength between the coating and the substrate is strong.
[0089] Figure 2 This is an indentation bonding strength test diagram of the Ti / TiAlSiN wear-resistant coating prepared in Example 2. It can be seen that the Ti / TiAlSiN wear-resistant coating has no cracks or shedding, indicating that the bonding strength between the coating and the substrate is strong.
[0090] Figure 3 This is a test diagram of the micron indentation of the Cr / CrCN wear-resistant coating prepared in Example 1. It can be seen that no cracks are generated in the indentation, indicating that the Cr / CrCN wear-resistant coating has good toughness and crack resistance, and the fracture toughness KIC ≥ 3MPa·m 1 / 2 .
[0091] Figure 4 This is a test diagram of the micron indentation of the Ti / TiAlSiN wear-resistant coating prepared in Example 2. It can be seen that no cracks are generated in the indentation, indicating that the Ti / TiAlSiN wear-resistant coating has good toughness and crack resistance, and the fracture toughness KIC ≥ 3MPa·m 1 / 2 .
[0092] Figure 5 This is a friction and wear curve diagram of the Cr / CrCN wear-resistant coating prepared in Example 1. It can be seen that the friction coefficient of the Cr / CrCN wear-resistant coating is extremely low, at about 0.08.
[0093] Figure 6 This is a friction and wear curve diagram of the Ti / TiAlSiN wear-resistant coating prepared in Example 2. It can be seen that the friction coefficient of the Ti / TiAlSiN wear-resistant coating is about 0.13.
[0094] The above test results indicate that the wear-resistant coating prepared by the present invention has good lubrication performance, uniform microstructure and excellent wear resistance.
[0095] It can be seen from the above embodiments that the present invention provides a wear-resistant coating for the inner wall of a slender tube and a preparation method thereof, comprising the following steps: cleaning the slender tube, then placing the ion source at the center of the slender tube, placing the target material in the slender tube, sealing both ends of the slender tube, setting a vacuum circuit and a gas circuit, and obtaining a tubular magnetron sputtering device; then sequentially performing ion cleaning, preparing a bonding layer and a nano coating on the above tubular magnetron sputtering device to obtain a wear-resistant coating, wherein the preparation of the bonding layer and the nano coating adopts high-power pulsed magnetron sputtering technology or deep oscillation magnetron sputtering technology. The nanohardness of the wear-resistant coating is 15-45GPa, H / E*≥0.1, uniformity ≥96%, H 3 / E* 2 ≥0.3, Rockwell indentation bonding strength ≥HF1, fracture toughness K IC ≥3MPa·m 1 / 2 , the friction coefficient is ≤0.3. The present invention places the ion source and the target material in a slender tube fitting, and the slender tube fitting is a vacuum chamber, which can adapt to the preparation of various slender tube inner wall coatings, and the process is flexible and adjustable.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a wear-resistant coating on the inner wall of a slender tube, characterized in that: The steps include: (1) cleaning the elongated tube, then placing an ion source at the center of the elongated tube, placing a target material in the elongated tube, sealing both ends of the elongated tube, setting a vacuum circuit and a gas circuit, and obtaining a tubular magnetron sputtering device; (2) sequentially performing ion cleaning on the tubular magnetron sputtering device, preparing a bonding layer and a nano coating, and obtaining a wear-resistant coating; The bonding layer and the nano coating are prepared by using a high-power pulsed magnetron sputtering technique or a deep oscillation magnetron sputtering technique.
2. The method for preparing the wear-resistant coating on the inner wall of the elongated tube according to claim 1, characterized in that: In the step (1), the length-to-diameter ratio of the slender tube is ≥12:1, the inner diameter is ≥40 mm, and the length is ≥500 mm.
3. The method for preparing the wear-resistant coating on the inner wall of an elongated tube according to claim 1 or 2, characterized in that: In the step (1), the target material comprises one or more of Cr, Ti, Al, TiAlSi, TiAl, TiVSi, TiSi, Si, CrAl and carbon.
4. The method for preparing the wear-resistant coating on the inner wall of the elongated tube according to claim 3, characterized in that: In the step (1), the length of the target material is the same as the length of the slender tube; and the ratio of the inner diameter of the slender tube to the diameter of the target material is 4:2-3.
5. The method for preparing the wear-resistant coating on the inner wall of an elongated tube according to claim 1, 2 or 4, characterized in that: In the step (2), during ion cleaning, the tubular magnetron sputtering device is first evacuated to a vacuum level of less than 1×10 -4 Pa then performs ion cleaning.
6. The method for preparing the wear-resistant coating on the inner wall of the elongated tube according to claim 5, characterized in that: The process parameters of the ion cleaning are: argon gas flow rate of 80 to 180 sccm, gas pressure of 0.2 to 3 Pa, voltage of -500 to 800 V, frequency of 80 to 120 kHz, and ion cleaning time of 30 to 90 min.
7. The method for preparing the wear-resistant coating on the inner wall of the elongated tube according to claim 4 or 6, characterized in that: In the step (2), high-power pulsed magnetron sputtering is started to prepare the bonding layer, and the process parameters are: pulse width is 1 to 5 μs, peak power is 6 to 8 kW, argon flow rate is 60 to 130 sccm, gas pressure is 0.3 to 2 Pa, voltage is -30 to -200 V, high energy bombardment is performed for 1 to 5 minutes, and then the voltage of the negative bias power supply is reduced to -60 to -100 V.
8. The method for preparing the wear-resistant coating on the inner wall of the elongated tube according to claim 7, characterized in that: In the step (2), deep oscillation magnetron sputtering is started to prepare the nano coating, and the process parameters are: pulse switching time ratio is 1-5μs / 10-50μs, average power is 0.5-2kW, gas pressure is 0.2-3Pa, argon flow rate is 50-180sccm, nitrogen flow rate is 40-180sccm, voltage is -20--100V, and preparation process time is 60-150min.
9. The wear-resistant coating prepared by the method for preparing the wear-resistant coating on the inner wall of an elongated tube according to any one of claims 1 to 8, characterized in that: The nano hardness of the wear-resistant coating is 15-45 GPa, H / E*≥0.1, uniformity≥96%, H 3 / E* 2 ≥0.3, Rockwell indentation bonding strength ≥HF1, fracture toughness K IC ≥3MPa·m 1 / 2 , friction coefficient ≤0.3.
Citation Information
Cited By
Magnetron sputtering device for preparing coating on inner surface of air cylinder
CN119932503A